1995
DOI: 10.1074/jbc.270.25.15085
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Endoplasmic Reticulum Chaperone Calnexin in Subunit Folding and Assembly of Nicotinic Acetylcholine Receptors

Abstract: The nicotinic acetylcholine receptor (AChR) is a pentameric complex assembled from four different gene products by mechanisms that are inadequately understood. In this study we investigated the role of the endoplasmic reticulum (ER)-resident molecular chaperone calnexin in AChR subunit folding and assembly. We have shown that calnexin interacts with nascent AChR alpha-subunits (AChR-alpha) in muscle cell cultures and in COS cells transfected with mouse AChR-alpha. In chick muscle cells maximal association of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 48 publications
5
75
0
2
Order By: Relevance
“…found that nascent AChR ␣-subunit binds to the molecular chaperone calnexin immediately after ␣-subunit synthesis (20). The time course of ␣-subunit-calnexin dissociation was observed to coincide with the conformational maturation of ␣-subunit, consistent with a role for calnexin in mediating ␣-subunit folding.…”
Section: Relationship Between Disulfide Bond Formation and The Interamentioning
confidence: 55%
See 3 more Smart Citations
“…found that nascent AChR ␣-subunit binds to the molecular chaperone calnexin immediately after ␣-subunit synthesis (20). The time course of ␣-subunit-calnexin dissociation was observed to coincide with the conformational maturation of ␣-subunit, consistent with a role for calnexin in mediating ␣-subunit folding.…”
Section: Relationship Between Disulfide Bond Formation and The Interamentioning
confidence: 55%
“…2 (left panel) shows the time course of AChR assembly under control conditions, as monitored by the accumulation of ␣-subunit immunoprecipitated with anti-␦-subunit antibody with increasing chase times. The ␦-subunit itself is not visible in [ 35 S]methionine-labeled preparations due to its diffuse migration as a heterogeneous band, high susceptibility to proteolysis, and nonspecific backgrounds in this region of the gel, as noted previously by ourselves (18,20) and others (43). However, the ␦-subunit is phosphorylated and is clearly visible in immunoprecipitates from cultures labeled with 32 P i (18).…”
Section: Dtt Treatment Blocks Achr Surfacementioning
confidence: 63%
See 2 more Smart Citations
“…Studies in transfected cells have helped in characterizing the interaction of nAChRs with chaperone proteins such as BiP [277,278] and calnexin [279][280][281]. Such studies have also helped to reveal the role of nAChR-interacting proteins such as 14-3-3 [282,283] and VILIP-1 [284] in regulating cell-surface expression of α4β2 nAChRs.…”
Section: Co-expression With Chaperones and Interacting Proteinsmentioning
confidence: 99%